"THE IMPACT OF FOREIGN AID ON POVERTY REDUCTION IN SUB-SAHARAN AFRICA: THE ROLE OF CORRUPTION AND ECONOMIC GROWTH" (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This study examines the relationship between economic growth, corruption, and foreign aid in Sub-Saharan Africa to answer the following research question: What is the impact of foreign aid on poverty reduction in Sub-Saharan Africa? Panel data from 2010 to 2023 was chosen for the analysis and Ordinary Least Squares regression model is employed. The independent variable is foreign aid, the dependent variable is poverty headcount ratio, and the control variables are GDP per capita and the Corruption Perceptions Index. The outcomes show that foreign aid falls short of its objective of reducing poverty in Sub-Saharan Africa. Furthermore, reduced corruption decreases the poverty rate, demonstrating its significance in the successful application of foreign aid. Finally, it was demonstrated that GDP per capita alone had almost no impact. Three policy recommendations were made: eliminate corruption, improve control over finances, and put strategies for sustainable growth into practice.